THE EFFECTIVENESS OF RECIPROCAL TEACHING STRATEGIS IN IMPROVING THE SPEAKING SKILLS - Aulia Nur Kirani; Muhammad Chairil Imran; Jusmaniar N (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
The purpose of this research is to find out whether reciprocal teaching is effective in improving the speaking skills of class VIII students of SMPN. 3 Mamuju. This study used Classroom Action Research methods which were carried out in 2 cycles, each cycle consisting of 4 stages, namely Planning, Action, Observation and Reflection. The subject of this research was students of SMPN 3 Mamuju class VIII-b, which consisted of 20 students. This research is useful for learning to speak, especially the discussion process so that it can be useful for obtaining input and efforts to improve students' speaking skills. The result of this research found that In cycle I, 7 out of 20 students (35%) which categories as law, got score more that 72 as Minimum Completeness Criteria (KKM). 18 out of 20 students (90.00%) which categories as success passed value of Minimum Completeness Criteria (KKM). This is proved by their participation in conversations and discussions, performance in front of the class, Pronunciation, Fluency, and confidence in Speaking. Moreover, the students were active and participated in the speaking teaching-learning process. Therefore it can be concluded that that the Reciprocal Teaching Strategy is effective in improving and maintaining students' speaking skills.